Corneal keratocyte transition to mesenchymal stem cell phenotype and reversal using serum-free medium supplemented with FGF-2, TGF-ß3 and retinoic acid - Sidney, Laura E.; Hopkinson, A. (Wiley, 2016)
Keratocytes of the corneal limbal stroma can derive populations of mesenchymal stem cells (MSC) when expanded in vitro. However, once a corneal MSC (cMSC) phenotype is achieved, regaining the keratocyte phenotype can be challenging, and there is no standardised differentiation medium. Here, we investigated the transition of keratocytes to cMSC and compared different supplements in their ability to return cMSC to a keratocyte phenotype. Immunofluorescence and RT-qPCR demonstrated in vivo keratocyte expression of ALDH3A1, CD34 and keratocan, but not any of the typical MSC markers (CD73, CD90, CD105). As the keratocytes were expanded in vitro, the phenotypic profile reversed and the cells expressed MSC markers but not keratocyte markers. Differentiating the cMSC back to a keratocyte phenotype using non-supplemented, serum-free medium restored keratocyte markers but did not maintain cell viability or support corneal extracellular matrix (ECM) production. Supplementing the differentiation medium with combinations of fibroblast growth factor-2 (FGF-2), transforming growth factor-β3 (TGF-β3) and retinoic acid (RA) maintained viability, restored expression of CD34, ALDH3A1 and keratocan, and facilitated production of abundant ECM as shown by immunofluorescent staining for collagen-I and lumican, alongside quantitative assays for collagen and glycosaminoglycan production. However, no differentiation medium was able to downregulate the expression of MSC markers in the 21-day culture period. This study shows that the keratocyte to MSC transition can be partially reversed using serum-free media and supplementation with RA, FGF-2 and TGF-β3 can enhance this effect. This is relevant for development of corneal regenerative strategies that require the production of a keratocyte phenotype.